Temporal trends in primary payers in pediatric heart transplant and association with long‐term survival. (7th February 2023) - Restaino, Kathryn; Zhang, Xuemei; Faerber, Jennifer A.; Rossano, Joseph W.; Burstein, Danielle; Wittlieb‐Weber, Carol A.; Lin, Kimberly Yee; Edelson, Jonathan B.; Edwards, Jonathan J.; O'Connor, Matthew J.
Abstract: Background: Pediatric heart transplantation (HT) is resource intensive. In adults, there has been an increase in the proportion of HTs funded by public insurance, with post‐HT outcomes inferior to those funded by private sources. Trends in the funding of pediatric HT and outcomes in children have not been described. Methods: We queried the United Network for Organ Sharing (UNOS) database for children (<18 years) listed for and undergoing HT between 2004 and 2021. We identified the primary payer at listing, HT, 1 year, and 1–5 years following HT. Trends were analyzed using generalized logit models. Multivariable‐extended Cox regression models were used to test the relationship between insurance type at the time of transplant and time to death or re‐transplant. Results: There were 6382 pediatric patients who underwent transplants and had either public or private insurance at the time of transplant. The percentage of patients with public insurance at the time of HT increased over time. Public insurance at the time of HT was associated with an increased risk of death or re‐transplant beyond 2 months after HT (adjusted HR at 6 months = 1.43, 95% CI: 1.13–1.81, p  = .003; adjusted HR at 9 months = 1.67, 95% CI: 1.17–2.37, p  = .004). Conclusion: There has been a statistically significant trend toward increasing public insurance for children awaiting, at the time of, and after HT. Black patients and those with public insurance at HT have worse long‐term outcomes. This study highlights ongoing disparities in pediatric HT and the need to focus efforts on achieving equitable outcomes.